Automated ablation of dental composite using an IR pulsed laser coupled to a plume emission spectral feedback system. Issue 7 (3rd May 2017) - Jang, Andrew T.; Chan, Kenneth H.; Fried, Daniel
Abstract : Objective: The purpose of this study is to assemble a laser system for the selective removal of dental composite from tooth surfaces, that is feasible for clinical use incorporating a spectral feedback system, a scanning system, articulating arm and a clinical hand‐piece, and evaluate the performance of that system on extracted teeth. Methods: Ten extracted teeth were collected and small fillings were placed on the occlusal surface of each tooth. A clinical system featuring a CO2 laser operating at 50 Hz and spectral optical feedback was used to remove the composite. Removal was confirmed using a cross polarized optical coherence tomography (CP‐OCT) system designed for clinical use. Results: The system was capable of rapidly removing composite from small preparations on tooth occlusal surfaces with a mean loss of enamel of less than 20 μm. Conclusion: We have demonstrated that spectral feedback can be successfully employed in an automated system for composite removal by incorporating dual photodiodes and a galvanometer controlled CO2 laser. Additionally, the use of registered OCT images presents as a viable method for volumetric benchmarking. Overall, this study represents the first implementation of spectral feedback into a clinical hand‐piece and serves as a benchmark for a future clinical study. Lasers Surg. Med. 49:658–665, 2017. © 2017 Wiley Periodicals, Inc.